Estudio de la variabilidad temporal y espacial de la pérdida de suelo en la dehesa (Extremadura, SO España) mediante lluvia simulada - Ceballos Barbancho, A.; Shanabel, S.; Cerdà, A. (Geographicalia, 2002)
The inain objective of this paper is to study the influence of the seasonal variability of tlze antecedent conditions in soil losses in a dehesa ecosystem, as well as an approach to its spatial variability. The experimental layout includes forty rainfall simulation experiments carried out in two different situa- tions: first on dry conditions, with degraded vegetation, and, second on wet con- ditions, with an important vegetation cover. The results indicate that the highest sediiilent concentrations are located in situations with bare soils, due to the effect of the drought and the soil remo- ved by grazing animals. The control of the process depends more to tlie sediment available on the soil surface than to the runoff transport capacity. From an spatial point of view, it liighlights the contrast between tlie low los- ses registered in the valley bottoms and the highest values measured in tlie areas more frequented by the livestock, where the degradation of the vege- tation cover and the removal of tlie soil material are continuous. Finally, although the rate of soil loss in the dehesa is low, it is important froin a qua- litative point of view because it affects to the inost fertile horizon in the soil profile
Keywords: Dehesa; rainfall simulation; runoff; Season; sediment concentration; soil loss